The Impact of Group Prenatal Care on Interpregnancy Interval - Keller, Justine M.; Norton, Jessica A.; Zhang, Fan; Paul, Rachel; Madden, Tessa; Raghuraman, Nandini; Stout, Molly J.; Carter, Ebony B. (American Journal of Perinatology, 2021)
Objective To evaluate whether participation in CenteringPregnancy group prenatal care is associated with decreased risk of an interpregnancy interval (IPI) ≤6 months.Study Design We conducted a retrospective cohort study of women enrolled in Missouri Medicaid from 2007 to 2014 using maternal Medicaid data linked to infant birth certificate records. Inclusion criteria were women ≥11 years old, ≥1 viable singleton delivery during the study period, residency in St. Louis city or county, and ≥2 prenatal visits. The primary outcome was an IPI ≤6 months. Secondary outcomes included IPI ≤12 months, IPI ≤18 months, postpartum long-acting reversible contraception (LARC) uptake, and postpartum LARC or depot medroxyprogesterone acetate (DMPA) uptake. Data were analyzed using descriptive statistics and logistic regression. Backward stepwise logistic regression was used to adjust for potential confounders including maternal age, race, obesity, nulliparity, marital status, diabetes, hypertension, prior preterm birth, and maternal education.Results Of the 54,968 pregnancies meeting inclusion criteria, 1,550 (3%) participated in CenteringPregnancy. CenteringPregnancy participants were less likely to have an IPI ≤6 months (adjusted odds ratio [aOR]: 0.61; 95% confidence interval [CI]: 0.47–0.79) and an IPI ≤12 months (aOR: 0.74; 95% CI: 0.62–0.87). However, there was no difference for an IPI ≤18 months (aOR: 0.89; 95% CI: 0.77–1.13). Women in CenteringPregnancy were more likely to use LARC for postpartum contraception (aOR: 1.37; 95% CI: 1.20–1.57).Conclusion Participation in CenteringPregnancy is associated with a significant decrease in an IPI ≤6 and ≤12 months and a significant increase in postpartum LARC uptake among women enrolled in Missouri Medicaid compared with women in traditional prenatal care.Key Points
Keywords: prenatal care; CenteringPregnancy; long-acting reversible contraception; prenatal visits; interpregnancy interval; family planning; Medicaid